Meta-analysis of breast cancer outcomes in adjuvant trials of aromatase inhibitors versus tamoxifen - Dowsett, Mitch; Cuzick, Jack; Ingle, Jim; Coates, Alan; Forbes, John; Bliss, Judith; Buyse, Marc; Baum, Michael; Buzdar, Aman; Colleoni, Marco; Coombes, Charles; Snowdon, Claire; et al. (Journal of clinical oncology, 2010)
To conduct meta-analyses of randomized trials of aromatase inhibitors (AIs) compared with tamoxifen either as initial monotherapy (cohort 1) or after 2 to 3 years of tamoxifen (cohort 2). Data submitted to the Early Breast Cancer Trialists' Collaborative Group were used in separate meta-analyses of two cohorts. Primary analyses involve postmenopausal women with tumors reported to be estrogen receptor positive. Log-rank P values are two-sided. Cohort 1 comprised 9,856 patients with a mean of 5.8 years of follow-up. At 5 years, AI therapy was associated with an absolute 2.9% (SE = 0.7%) decrease in recurrence (9.6% for AI v 12.6% for tamoxifen; 2P < .00001) and a nonsignificant absolute 1.1% (SE = 0.5%) decrease in breast cancer mortality (4.8% for AI v 5.9% for tamoxifen; 2P = .1). Cohort 2 comprised 9,015 patients with a mean of 3.9 years of follow-up. At 3 years from treatment divergence (ie, approximately 5 years after starting hormonal treatment), AI therapy was associated with an absolute 3.1% (SE = 0.6%) decrease in recurrence (5.0% for AI v 8.1% for tamoxifen since divergence; 2P < .00001) and an absolute 0.7% (SE = 0.3%) decrease in breast cancer mortality (1.7% for AI v 2.4% for tamoxifen since divergence; 2P = .02). There was no convincing heterogeneity in the proportional recurrence reduction with respect to age, nodal status, tumor grade, or progesterone receptor status and no indication of an increase in nonbreast deaths with AIs in either cohort. CONCLUSION AIs produce significantly lower recurrence rates compared with tamoxifen, either as initial monotherapy or after 2 to 3 years of tamoxifen. Additional follow-up will provide clearer information on long-term survival.